2018
DOI: 10.1007/s12134-018-0605-x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Minority Health and Employment: Ethnic Differences in the Protective Effect of Close Social Ties

Abstract: First-and second-generation Turkish and Moroccan migrants living in the Netherlands have a disproportionate incidence of health problems and relatively low employment rates. Health problems are an obstacle to employment, yet there is no one-to-one correspondence between health problems and capability to work. Social ties can reduce the negative impact of health problems on employment by providing social support and providing the comfort of feeling embedded in a close social circle. In this study, we examine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…It has been found that economic insecurity; the denial of access to decent jobs; and the low quality health care, housing, and educational services provided by countries to their migrant populations can even be described as a human rights violation. The violation of human rights significantly hinders the development of belonging, affiliation, approval, and recognition associated with a host culture [ 1 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that economic insecurity; the denial of access to decent jobs; and the low quality health care, housing, and educational services provided by countries to their migrant populations can even be described as a human rights violation. The violation of human rights significantly hinders the development of belonging, affiliation, approval, and recognition associated with a host culture [ 1 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resilient attitudinal dispositions in migrant students may be especially related to the quality of bonds and perceived social support in family and educational contexts. Some studies suggest that parents and teachers can be important models of resilience, favoring the social integration and participation of their children or students and the development of meaningful bonds with their peers, even when an adverse environment exists [ 40 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Although resilience is rarely the result of in-school interventions alone, the various programs/training, such as Psychosocial Structured Activities [ 74 ] ‘Be yourself and have a ball’ [ 75 ], and the Hong Kong Healthy School Award [ 76 ], converge in focusing their efforts on strengthening student engagement with school and increasing personal skills.…”
Section: Discussionmentioning
confidence: 99%